(untitled) (Orfeu, 2021)
Although Heinrich Schenker certainly changed his mind about many topics, he never waivered in his belief that 1) current ways to explain modulation were fundamentally flawed; and 2) that modulation is best learned by improvising preludes and fantasies. To explain these points, Part I reconsiders Schenker’s critique of Max Reger’s Beiträge zur Modulationslehre (1903) and Salomon Jadassohn’s Die Kunst zu Modulieren und zu Präludieren (1890) and describes three types of modulation endorsed by Schenker in his Harmonielehre (1906): 1) [diatonic] reinterpretation; 2) chromaticism; and 3) enharmonicism. Part II then shows how Schenker not only dispensed with the traditional concepts of relative, close, and distant keys, but he eventually proposed that modulations arise at the foreground for contrapuntal, even motivic reasons. Finally, Part III uses Schenker’s claims about modulating and preludizing to analyze Beethoven’s “Two Preludes” in C major, Op. 39, both of which modulate “through all twelve major keys.”